Pelatihan Perhitungan Harga Pokok Produk Bank Sampah di Kecamatan Rumbai - Yesi Mutia Basri; Hariadi Yasni; Vera Oktari; Damara Putri Hestia Indrapraja (Yumary: Jurnal Pengabdian kepada Masyarakat, 2022)
Purpose: This community service activity aims to train Waste Bank managers in determining the cost of Waste Bank products. Method: The method in this activity is a lecture followed by a discussion and simulation of calculating the cost of the product. The target audience is the manager of the Waste Bank. Results: The results of service activities increase the understanding of Waste Bank managers in calculating the cost of production, determining the selling price, and calculating the profit or loss on product sales. Conclusion: The initial survey shows that many waste bank managers do not understand how to calculate product cost, selling price, and profit/loss. With this activity, there is an increase in the understanding of waste bank managers in determining the selling price of their products. This activity has benefits in addition to creating a clean environment and contributing to improving the community's economy.